KOMPETENSI SUMBER DAYA MANUSIA KOPERASI DI KECAMATAN KLUNGKUNG - Nengah Aristana; Wayan Arta Artana (Forum Manajemen, 2015)
Bali today is experiencing a growth in the number of cooperatives, butthe growth of the cooperativeis not followed by the quality ofthe cooperative it self.Particularly in Klungkung cooperatives is still having problems in the field of humanresources cooperatives, which are owned by the board still does not have sufficientcompetence because of the lack of understanding of competence in accordance withthe needs of existing cooperatives. Therefore, this research intends toformulate thefactors thatinfluence cooperative human resource competencies that will be able tobe used as the basis in finding or developing its human resources. In the extraction of the factors thatmade the overall show variables can explain the variety ofform factors. After that is the determination of the number offactors, which deserve to becalled whenthe factor has a value of more than 1 can be computed as a factor, sothat only four factors were formed. Form factor given the name 1) Mastery of work,2) Self-awareness, 3) Personal capability and 4) Individual excellence. Assessmentsfactorsindicate that the model has an accuracy of 61% on the error rate or alphaof 5%.